Asymmetric real exchange rate and foreign direct investment determinants: An empirical study of Malaysia - Wong, Hock Tsen (Malaysian Finance Association, 2022)
This study examines the impact of macroeconomic variables and also the asymmetric impact of the real exchange rate on foreign direct investment (FDI) by country in Malaysia, namely Japan, the United States of America, Singapore, Germany Taiwan, Korea, Australia, the United Kingdom, Hong Kong and India. Moreover, this study investigates macroeconomic determinants of FDI of those countries as a group in Malaysia. The promotion of FDI shall consider potential heterogeneous of FDI from different country as the source or type of FDI likely different from country. There are not many studies investigate the asymmetric impact of the real exchange rate on FDI. Data: The data is yearly from 1980 to 2017, except for Korea the data is from 1981 to 2017 due to the availability of the data begins from 1981. The importance of macroeconomic variables as FDI determinants by country in Malaysia is examined by the autoregressive distributed lag model (ARDL) approach. Conversely, the importance of macroeconomic variables as FDI determinants of those countries as a group in Malaysia is estimated by the system generalized method of moments (GMM) of the Arellano-Bond estimator. The results of the autoregressive distributed lag model (ARDL) approach show the determinants of each country are not the exactly the same. The results of the non-linear autoregressive distributed lag model (NARDL) approach shows that there is some evidence of the asymmetric impact of the real exchange rate on FDI in the long run and short run. The results of the system generalized method of moments (GMM) of the Arellano-Bond estimator reveal that the real exchange rate, positive real exchange rate, negative real exchange rate, real national income, trade openness and real average wage are found to be the main macroeconomic determinants of FDI from Japan, the United States of America, Singapore, Germany Taiwan, Australia, the United Kingdom, Hong Kong and India. The implications for policymakers are to promote a dynamic competitive advantage in the home country and therefore policymakers need to pay more attention to their macroeconomic policies to reduce production and transaction costs of FDI